Trening kontroli motorycznej w niskim obciążeniu u kobiet z przewlekłym bólem kręgosłupa lędźwiowego o charakterze zwyrodnieniowym i przeciążeniowym = Low-load motor control training in women with chronic degenerative and overload pain in the Lumbar spine - Ulikowski, Michał; Wojciechowski, Jarosław; Leszczyński, Ryszard; Lewandowski, Jacek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to provide information on the efficiency of low-load motor training in the patients with chronic pain in the lumbar spine. Three hypotheses were put forward. The first one says that motor control training reduces lower back pain; the second one is related to the change in pain intensity; the third hypothesis refers to the efficiency of sanatorium treatment with and without motor training. The study involved 30 women.
Keywords: ból dolnego odcinka kręgosłupa; stabilizacja centralna; kontrola motoryczna; leczenie sanatoryjne; lower back pain; core stability; motor control; sanatorium treatment